Low Valent N-Coordinated Cations and Dications of Heavier Group 14 Elements: Lewis Acids or Bases? - Jambor, Roman; Novák, Miroslav (Wiley-VCH, 2023)
Low-valent N-coordinated cations and dications of heavier group 14 elements are of great interest in recent years. Their unique electronic structure gives them an ambiphilic character, as they contain both a lone electron pair and an empty p-orbital on the central metal atom. Thanks to their nucleophilic character, these compounds can act as ligands in transition metal chemistry, and conversely, their electrophilic character allows them to interact with a wide range of organic substrates and thus replace catalysts based on transition metal complexes in many chemical transformations. The aim of this article is to summarize the synthesis of N-coordinated ionic compounds of heavier group 14 elements with their subsequent reactivity towards various nucleophiles and electrophiles.
Nízkovalentní N-koordinované kationty a dikationty těžších prvků 14. skupiny: Lewisovy kyseliny nebo zásady?
Keywords: tetryliumylidenes; N-donor ligands; ambiphilicity; homogeneous catalysis; group 14 elements; 14. skupina; N-chelatující ligand; kationt; nukleofil; elektrofil